Boiling sand, metallic fire: Technopolitics and temporal form in an Idaho nuclear waste accident. (1st July 2022) - IALENTI, VINCENT
ABSTRACT: In April 2018 four drums of depleted uranium sludge burst open at a US Department of Energy facility at Idaho National Laboratory. This echoed a previous incident in 2014, when a drum erupted with fire and spewed radionuclides at a nuclear waste repository in New Mexico. Such "drum breach" accidents have been characterized in official reports as "isolated events, " and as "self‐initiated" and "spontaneous." Yet these descriptions misrepresent a temporal tension at the heart of their causation: during the Cold War, nuclear weapons production created latent socioecological hazards that, decades later, too often manifest during waste cleanup. This tends to result from 21st‐century scheduling pressures, fraught labor relationships, and neoliberal subcontracting arrangements. Thus, if we examine the temporal form taken by US nuclear technopolitics, we can recast drum breach accidents not as stand‐alone events, but as outcomes of systemic incentives to speed up waste‐cleanup projects beyond their organizational capacity without commensurately expanding their safety or oversight mechanisms. [ nuclear waste, technopolitics, accidents, neoliberalism, temporality, security, Idaho, United States ]